Contribuição da avifauna como indicador da integridade ambiental na estação experimental de Holambra - SP - Santos, Erika Nakata dos (2014)
Feeding a growing population is a very important role of farmers, beside that they must also provide raw materials for many industries and ethanol, all in a healthy and sustainable way. Also lies in their hands the great responsibility of maintaining a conservation area on their property to ensure the quality of the soil and water and the conservation of the flora and fauna. The new forest act - Law 12.651 of May 25th, 2012 - states that all farms must maintain areas of preserved natural vegetation. The Holambra Experimental Station - cited in this dissertation - follows the current Brazilian legislation. This Agricultural Experimental Station is a small property located in Holambra city and belongs to the multinational company Syngenta. There pesticides and seeds are tested for future registration or just for research. This property is in accordance with the good agricultural practices so that erosion, soil and water contamination are avoided. The conservation areas, including native vegetation and reforestation areas, are maintained without any anthropogenic activities. Bird survey was made in the conservation areas in this small property in 2003, 2005, 2010 and 2013. The data indicated a trend of increasing diversity and species richness over the years. Moreover, it was seen an increase of forest birds, waterbird and 'cerrado' birds, as well as birds with a less opportunistic profile and medium sensitivity to anthropogenic changes. These data indicate a supportive change in the area environmental index .Despite the intense use of agricultural fertilizers and pesticides at the Experimental Station no dead or intoxicated birds were found. In addition, several birds from the top of the food chain, which could accumulate toxins, grew in species richness along the surveys. These data demonstrate that the activities of the Agricultural Experimental Field are not impacting the birds and the careful maintenance of the conservation area and its surroundings can contribute to the conservation of local biodiversity.